Thrombopoietic status of patients on haemodialysis. (16th February 2016) - Bat, Taha; Bat, Betul E.; El‐Moghraby, Ahmed; Patel, Samir; Feng, Xingmin; Dunbar, Cynthia E.; Sarac, Erdal
Summary: Thrombocytopenia is a potential dialysis‐related treatment complication. Developments in bio‐compatible dialyser membranes have decreased the occurrence of thrombocytopenia. We investigated whether thrombopoiesis is impaired in haemodialysis patients by measuring the thrombopoietin level and absolute immature platelet number (AIPN) in the blood of patients undergoing haemodialysis. Samples were collected from the dialysis tubing pre‐ and post‐ haemodialysis in a cohort of 45 well‐characterized haemodialysis patients. Thrombopoietin levels and AIPN increased following haemodialysis, despite no change in platelet count. Observed increase in release of immature platelets from the bone marrow following haemodialysis indicates possible complement activation secondary to interaction between blood constituents and the dialysis membrane.